Determination of liquid product distribution route using clark and wright saving and tabu seacrh algorithm for a milk industry in indonesia - Adianto, Hari; Ilman Riawan, Adnan; Susanto, Edi (International Journal of Engineering and Technology, 2018)
Distribution system is a bridge between producers and consumers where the level of importance is very high and the need for calculation of time and capacity of the determination of the route to be made. Therefore, it is necessary to propose effective and efficient distribution route determination by using Clarke & Wright and Tabu Search method and application proposal which must be in company. Based on the proposed distribution determination can determine the route of the achieved distribution channels, the efficiency of time and distance by taking into account the capacity, speed, route, and others. The Clarke & Wright and Tabu Search methods are used to determine the route of distribution routes and improvements on the routes route of distribution of ultra-liquid dairy products by considering the capacity aspect, vehicle speed, loading and unloading time, time matrix, distance matrix, distance saving, and iterations Contained in the method. Based on the calculation results can be concluded that the proposed determination of distribution feasible applied to the company because the comparison of time and distance performance resulting savings and improvements in time and distance by reducing the amount of time achieved on each route and tour contained in the applicable time horizon.Â Â